Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Journal of Tropical Pharmacy and Chemistry, 2012)
J. Trop. Pharm. Chem. 2012. Volume 1 Nomor 4 Team, Front cover, Editorial information, Table of Content, Back Cover